АЛГОРИТМ КЕРУВАННЯ СИМЕТРУВАЛЬНИМИ ПРИСТРОЯМИ ЗА БАГАТОКРАТНОЇ НЕСИМЕТРІЇ В РОЗПОДІЛЬНИХ МЕРЕЖАХ - Бурбело, М.Й.; Девятко, М.В.; Войтюк, Ю.П. (Інститут електродинаміки НАН України, Київ, 2023)
The article proved balancing compensation algorithm of control devices for repeated asymmetry in the distribution networks in the event of a significant asymmetry loads and supply voltage. References 3, figures 5.